STUDY OF THE LEVEL OF ELECTROMAGNETIC INTERFERENCE IN A NETWORK WITH POWER TRANSFORMERS OF VARIOUS CAPACITIES UNDER ASYMMETRIC NATURE OF THE LOAD - A. I. Antonov (Известия высших учебных заведений: Проблемы энергетики)
In the article results of researches of levels of electromagnetic disturbances on the unbalance voltage factors on the reverse sequence in a 10 / 0.4 kV network with asymmetric sharply variable load are presented with power transformers of different power.